Optimización de las mediciones de la calidad del agua de producción de la tecnología Smart Water Quality (SWQ) de la empresa JPT/Ecopetrol mediante el Machine Learning (2024)
In the course of this study, developed at the Saara treatment plant, located in the municipality of Puerto Gaitán, Meta, and belonging to the operator Frontera Energy, which receives production water from the Quifa and Rubiales fields, the implementation of SWQ technology. This innovative technology allows the measurement of various water quality parameters in real time, providing valuable information on the quality of the water entering and treated at the plant. The process began with the planning of multiple meetings to identify the optimal and appropriate points for the installation of the technology. Subsequently, two engineers were sent to carry out the installation, who, in addition to executing the installation, continuously supervised the equipment, monitoring its operation and resolving any problems that may arise with the sensors. This monitoring lasted for approximately 20 consecutive days, focusing especially on the end point of the plant, known as the permeate pool, where the treated and filtered water reaches ideal conditions for use in injection into crops, in accordance with the Resolution. 1256 of 2021.